2022
DOI: 10.1021/acsnano.2c01014
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design of Lasso-like Self-Assembling Anticancer Peptides with Multiple Functions for Targeted Self-Delivery and Cancer Treatments

Abstract: Anticancer peptides are promising drug candidates for cancer treatment, but the short circulation time and low delivery efficiency limit their clinical applications. Herein, we designed several lasso-like self-assembling anticancer peptides (LASAPs) integrated with multiple functions by a computer-aided approach. Among these LASAPs, LASAP1 (CRG­DKG­PDC­GKA­FRR­FLG­ALF­KAL­SHLL, 1–9 disulfide bond) was determined to be superior to the others because it can self-assemble into homogeneous nanoparticles and exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Thus, the Lys 5 –Gly 6 bond is easily accessible for proteolytic cleavage, which releases the NRP-1-recognizing CendR/K sequence (CRGDK). On the other hand, the solvent exposure of the Cys 9 carboxylate explains why the bioconjugation of this group with bulky molecules, for either therapeutic or diagnostic purposes, is safely permitted. Both of these findings strengthen the reliability and increase the scientific impact of the obtained atomistic i RGD–integrin binding complexes.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, the Lys 5 –Gly 6 bond is easily accessible for proteolytic cleavage, which releases the NRP-1-recognizing CendR/K sequence (CRGDK). On the other hand, the solvent exposure of the Cys 9 carboxylate explains why the bioconjugation of this group with bulky molecules, for either therapeutic or diagnostic purposes, is safely permitted. Both of these findings strengthen the reliability and increase the scientific impact of the obtained atomistic i RGD–integrin binding complexes.…”
Section: Resultsmentioning
confidence: 93%
“…Over the past decade, the tumor-homing i RGD ( 1 ) peptide has emerged as a powerful tool for anticancer therapy, ,,, due to its high tropism for cancer tissues and the possible coadministration with a plethora of chemotherapeutic agents. In this article, we provide unprecedented data about the biological and structural aspects of i RGD’s mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DLS test results showed that the hydrodynamic diameter and zeta potential of the SP–Van@IR780 NPs were ∼230 and 15.77 mV, respectively (Figures B, S5). Due to the shrinkage of the nanoparticles in the dry state during TEM sample preparation, the average size from TEM image was smaller than the hydrodynamic diameters measured by DLS. The size stability of SP–Van@IR780 NPs in a normal physiological environment was evaluated. As shown in Figure C, there was no obvious change in the particle size within 10 days, indicating that the SP–Van@IR780 NPs would have good stability in the in vivo circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Pei et al designed some lasso-like self-assembling anticancer peptides (LASAPs) which can self-assemble into nanoparticles in solution, combined multiple tumor-targeting strategies for targeted cancer treatment, and the self-assembled LAS-APs showed resistance to various proteases and had longer in vivo half-lives than the effector peptide PTP-7b. [77] Wallace et al [78] demonstrated that a prodrug colistin methanesulfonate with better self-assembling ability showed much higher stability in solution than colistin. Li et al [79] modified the antimicrobial peptide halictines-2 (HAL-2) with cholesterol to obtain a self-assembling peptide HAL-C that can form nanoparticles in solution, and it showed much improved serum stability and in vivo antitumor activity.These researches pave the way to the clinical applications of self-assembling peptide drugs, which could be an effective strategy to solve the stability problem.…”
Section: Self-assembling Of Therapeutic Peptidesmentioning
confidence: 99%